2009
DOI: 10.1007/s11127-009-9440-0
|View full text |Cite
|
Sign up to set email alerts
|

Does economic freedom cause prosperity? An IV approach

Abstract: Economic freedom, Prosperity, Policies, Institutions, Instrumental variables, O1, O43,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(61 citation statements)
references
References 61 publications
1
55
0
2
Order By: Relevance
“…Farr, Lord and Wolfenbarger (2008) analysed the causality between economic freedom and growth on a sample of 98 countries and their results show that economic freedom Granger-causes economic growth. Faria and Montesinos (2009) found a "robust association between economic freedom and prosperity". In their literature review on this subject using the Economic Freedom of the World index, Hall and Lawson (2014) indicate that over two-thirds of the existing studies found that economic freedom is related to positive outcomes such as faster growth, better living standards, and more happiness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Farr, Lord and Wolfenbarger (2008) analysed the causality between economic freedom and growth on a sample of 98 countries and their results show that economic freedom Granger-causes economic growth. Faria and Montesinos (2009) found a "robust association between economic freedom and prosperity". In their literature review on this subject using the Economic Freedom of the World index, Hall and Lawson (2014) indicate that over two-thirds of the existing studies found that economic freedom is related to positive outcomes such as faster growth, better living standards, and more happiness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Because legal systems were transplanted throughout the world through the colonization efforts of a small number of Western European nations, legal tradition has been used as an instrument for institutions by researchers (e.g., Berggren & Jordahl, 2006;Faria & Montesinos, 2009). It is plausibly a valid exogenous instrument for institutions so long as legal tradition only impacts development through institutions and only former colonies that inherited a legal system from their colonizer are included in the sample.…”
Section: Theoretical Foundations For Identifica-tion Strategymentioning
confidence: 99%
“…The same methodology is also popular as a robustness check in cross-section studies that use IV estimation. For example, Crowe (2010) uses it to estimate the relationship between IT adoption and the quality of private sector forecasts, Faria and Montesinos (2009) to estimate the relation between growth, income level and freedom indexes; and Alcala and Ciccone (2004) for the link between trade and productivity. Other papers use a first-stage test of the F -statistic check with a critical value of 10.…”
Section: Literature Reviewmentioning
confidence: 99%